Survival and growth of Orientia tsutsugamushi in conventional hemocultures - Dittrich, S; Card, E; Phuklia, W; Rudgard, W; Silousok, J; Phoumin, P; Bouthasavong, L; Azarian, S; Davong, V; Dance, D; Vongsouvath, M; Phetsouvanh, R; et al. (Centers for Disease Control and Prevention, 2016)
Orientia tsutsugamushi, which requires specialized facilities for culture, is a substantial cause of disease in Asia. We demonstrate that O. tsutsugamushi numbers increased for up to 5 days in conventional hemocultures. Performing such a culture step before molecular testing could increase the sensitivity of O. tsutsugamushi molecular diagnosis.